The Foley Grail - Ament, Vanessa Theme (Elsevier, 2011)
Create custom sound effects that are the mainstay of soundtracks for films, broadcast, animation and games. Learn how Foley is designed, crafted and edited for any project- right down to the nuts and bolts of spotting, cueing, and performing sounds. An array of techniques is illustrated with artists presenting their own methods for selecting and handling props, "walking" various characters, and other tricks of the trade. Various renowned artists, editors and mixers contribute stories and perspectives on what is necessary for a film or media project, and how technology has changed the craft over the years. The Foley stage is discussed in detail, with illustrations to assist you in designing your own stage, whatever the size. The companion DVD includes video demonstrations of Foley Artists at work, along with illustrated techniques for the novice.